2020
DOI: 10.3389/fphar.2020.00284
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Pharmacology-Based Analysis for Antidepressant Mechanism of Chinese Herbal Formula Xiao-Yao-San

Abstract: Clinical studies and basic science experiments have widely demonstrated the antidepressant and anxiolytic effects of the herbal formula Xiao-Yao-San (XYS). However, the system mechanism of these effects has not been fully characterized. The present study conducted a comprehensive network pharmacological analysis of XYS and sorted all pharmacologically active components (149) through the TCMSP webserver. Then, all potential molecular targets (449) were predicted, of which there were 99 genes clearly related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…To explore whether XYS could suppress the lipid accumulation induced by CORT, we generated an ox-LDL and CORTinduced stress model in rat PMs following the treatment of XYS-containing serum. Our results showed that CORTinduced stress inhibited proliferation and increased lipid accumulation in PMs, which was similar to the results of previous studies (24,25). We also found that serum including XYS could dose-dependently increase proliferation, decrease lipid accumulation, and elevate TC level in CORT-induced PMs.…”
Section: Discussionsupporting
confidence: 91%
“…To explore whether XYS could suppress the lipid accumulation induced by CORT, we generated an ox-LDL and CORTinduced stress model in rat PMs following the treatment of XYS-containing serum. Our results showed that CORTinduced stress inhibited proliferation and increased lipid accumulation in PMs, which was similar to the results of previous studies (24,25). We also found that serum including XYS could dose-dependently increase proliferation, decrease lipid accumulation, and elevate TC level in CORT-induced PMs.…”
Section: Discussionsupporting
confidence: 91%
“…The expression of P-Akt in the hippocampus of sodium arseniteexposed rats was significantly lower than that in the control group (Srivastava et al, 2018). Naijun Yuan et al also found that Xiaoyaosan could increase the P-AKT/AKT ratio in cortisolinduced PC-12 cells (Yuan et al, 2020). Decreased Akt activity and decreased extracellular regulatory kinase activity coexist in depression, and autopsy studies have demonstrated that the activity of the PI3K-Akt signaling pathway is decreased in suicidal patients with major depression (Karege et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…at a ratio of 5:5:5:5:5:5:4:1. Xiaoyaosan (batch number J2447) was provided by Jiuzhitang Co., Ltd. (Changsha, China) and was prepared as previously described (Yuan et al, 2020). One gram of fine powder of Xiaoyaosan was obtained from 2.10 g of raw herbs.…”
Section: Preparation Of Xiaoyaosanmentioning
confidence: 99%
“…Systems pharmacology is an emerging systematic methodology that combines oral bioavailability screening, multiple drug targets prediction and validation, and network pharmacology, providing a holistic approach to explore the targets and mechanisms of TCM. In recent years, systems pharmacology has been widely used to reveal the potential mechanism of TCM formulas ( Liu et al, 2016 ; Yuan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%